Product Policy in Europe: New Environmental Perspectives - Oosterhuis, Frans; Rubik, Frieder; Scholl, Gerd (Environment & Policy, 1996)
Product Policy in Europe: New Environmental Perspectives presents an overview and assessment of a relatively new area of environmental policy in Europe. Whereas the more 'traditional' environment policy mainly deals with individual emissions, waste and substances, product policy is a more comprehensive approach addressing the environmental impacts of products during their whole life cycle. The study reviews the current state of affairs and the prospects for product policy in the EU and Switzerland. It shows the relationship with other areas of environmental policy and the potential role of new instruments and approaches. Four case studies (on paint, batteries, public procurement and eco-labelling) illustrate the barriers and opportunities of product policy. Environmental policy makers and policy analysts will find useful information and recommendations in this book. It is also written for those who have a professional interest in reducing the environmental impact of products, including marketing managers, product developers, procurement officers and staff members of environmental and consumer organisations, standardisation and certification institutions, etc